Fuzzy linguistic control systems for process control applications - Singh Y.P.; Ahmad N. (My University, 2025)
The paper presents design and tuning of real-time Fuzzy Logic/Linguistic Controllers (FLC) for real-time process control applications. Normally rule set/base for controllers are derived using heuristics and human operator experience with the plant, and basic engineering knowledge about the process dynamics. An alternative procedure based on the desired response of the process to derive control rules is investigated. The performance of the FLC is demonstrated by its application to the control of a laboratory liquid level rig for various set of values of scale factors (tuning parameters). Experimental results are given and a comparison is made with classical Proportional-Integral (PI) control techniques to demonstrate the performance of FLC. © 1996 Taylor & Francis Group, LLC.